The effect of sexual victimization on attachment in emerging adulthood: An analysis of an African-American sample. Issue 1 (January 2021) - Watts, Stephen; Evans, Sara Z; Simons, Leslie G; Simons, Ronald L
Research has consistently shown that sexual victimization during childhood and adolescence can lead to negative outcomes. However, little research to date has sought to test whether these experiences can shape security of attachment in adulthood, an important concept in attachment theory. Utilizing a longitudinal community sample of African Americans, the current study tested whether sexual victimization during childhood and adolescence correlated with security of attachment in emerging adulthood while controlling for parenting. Results of regression analyses showed that sexual victimization did correlate with greater insecurity of attachment in emerging adulthood while controlling for parenting among females, but not males. Implications of these findings for policy and theory are discussed.